Frequency of Dyslipidemia in Patients Having Subclinical Hypothyroidism - Shah Zeb; Shafaq Naz; Najeeb Ullah (Gandhara University, 2016)
INTRODUCTION Thyroid hormone by binding to the thyroid hormone receptors affects metabolism and growth in nearly all tissues of the body. Thyroid hormones play vital role in the synthesis and metabolism of lipids. The reduced secretion of thyroxine (T4) and triiodothyronine (T3) from the thyroid gland results in hypothyroidism. The subclinical hypothyroidism (SH) is term used for the condition in which there is small elevation of thyroid stimulating hormone (TSH) in the presence of normal thyroid hormone levels. Disorders of thyroid gland are the second most common endocrine abnormalities globally after diabetes mellitus. OBJECTIVE To determinethe frequency of dyslipidemia in patients having subclinical hypothyroidism. METHODOLOGY This study was conducted at Naseer Teaching Hospital, Peshawar. Duration of the study was one years and the study design was descriptive cross sectional study. The total sample size was 136 patients presenting with subclinical hypothyroidism taking 34.31% proportion of dyslipidemia in subclinical hypothyroid patients12, 95% confidence interval and 8 % margin of error; using WHO software for sample size calculation. More over consecutive (non-probability sampling) technique was used for sample collection. RESULTS In this study mean age was 40 years with SD 1.26. Sixty three percent patients were female and 37% patients were male. Seventy percent patients had dyslipidemia while 30% patients didn't have dyslipidemia. CONCLUSION The current study shows that the incidence of dyslipidemia was found to be in patients having subclinical hypothyroidism.